Overview of the Level of Compliance of Outpatients in the Pulmonary Polyclinic Against the Use of Antibiotics in HKBP Balige Hospital - Kurniasari, Heny; Yusuf, Faisal; Ulla, Ully Widya Rochmatil; Tambunan, Masrina Nurmayani (Institute of Accounting Research and Novation (IARN), 2025)
Overview of the Level of Compliance of Outpatients in the Pulmonary Polyclinic Against the Use of Antibiotics in HKBP Balige Hospital Compliance with antibiotic use in Indonesia is much more and worrying because the use of inappropriate doses and therapy times can cause problems of increasing resistance to antibiotic use, patient compliance with antibiotic use greatly affects the occurrence of resistance. This study aims to determine the level of patient compliance with antibiotic use at HKBP Balige Hospital. This study is a descriptive study, which describes the percentage of patient compliance with antibiotic use at HKBP Balige Hospital. The results of the study obtained, from the number of respondents as many as 60 people who were compliant as many as 59.10% and those who were not compliant as many as 40.90%. The conclusion of this study was obtained Level of Patient Compliance with Antibiotic Use In HKBP Balige Hospital is included in the compliant category. Suggestions for HKBP Ballige Hospital to maintain and improve services in providing drug information.